Comprehensive evaluation of the phytoremeditical ability of a number of agricultural crops for the restoration of polluted soils with heavy metals - Loseva, Ludmila P.; Krupskaya, Tatyana K.; Anuchin, Sergei N.; Anufrick, Slavamir S. (Journal of the Belarusian State University. Ecology, 2020)
During the work, the method of X-ray fluorescence analysis (XRF) has been used, which allows analyzing the content of various chemical elements from sulfur to uranium in samples of various nature (soil, plants). This method allows analyzing samples without complicated and lengthy sample preparation. In the course of work, model systems for heavy metals («soil−lead», «soil−cadmium», «soil−cadmium−lead») within the limits of 1−3 maximum permissible concentrations (MPC) for growing colza & flax have been compiled, bioelement gross concentrations have been determined. As a result of the work, one of the possible ways of removing heavy metals (HM) from contaminated soils, monitoring the environmental safety of a soil cover, as well as the opportunity to assess the phytoremediation ability of agricultural crops are proposed. A quantitative assessment of the content of trace and macroelements in the sod-podzolic soil as well as in model compositions based on it is presented. Bench studies on the cultivation of technical colza and flax on the proposed mixtures have been carried out. It has been shown that different concentrations of cadmium and lead have different effects on seed germination and plant growth dynamics. An increase in the concentration of heavy metals in the soil reduces the percentage of seed germination. Seed germination on the clean sod-podzolic soil is the highest – 80 %. The degree of the environmental safety of soils before and after the cultivation of technical colza and flax has been assessed. In some cases, the cultivation of technical colza and flax made it possible to reduce the total soil pollution by 3.1 times. It is shown that during the cultivation of industrial crops, metals are intensively absorbed and largely accumulate in the aboveground organs of plants. After harvesting the phytomass, the level of soil pollution risk is significantly reduced. Thus, the removal of chemical elements from the soil with industrial crops contributes to its self-cleaning. The results of the study will make it possible to expand the range of optimal crops for the phytoremediation of the soils contaminated with lead and cadmium.
Keywords: X-ray fluorescence analysis; soil; heavy metals; agricultural crops; restoration of polluted soils